Efficient incremental data backup of unison synchronize approach - Prakai Nadee; Preecha Somwang (Bulletin of Electrical Engineering and Informatics, 2021)
Data communication and computer networks have enormously grown in every aspect of businesses. Computer networks are being used to offer instantaneous access to information in online libraries around the world. The popularity and importance of data communication has produced a strong demand in all sectors job for people with more computer networking expertise. Companies need workers to plan, use and manage the database system aspects of security. The security policy must apply data stored in a computer system as well as information transfer a network. This paper aimed to define computer data backup policies of the Incremental backup by using Unison synchronization as a file-synchronization tool and load balancing file synchronization management (LFSM) for traffic management. The policy is to be able to perform a full backup only at first as a one time from obtaining a copy of the data. The easiest aspect of value to assess is replacement for restoring the data from changes only and processing the correct information. As a result, the new synchronization technique was able to improve the performance of data backup and computer security system.